Relationships between changes in lateral vestibulospinal tract excitability and postural control by dynamic balance intervention in healthy individuals: A preliminary study - Shiozaki, Tomoyuki; Okada, Yohei; Nakamura, Junji; Ueta, Kozo; Tanaka, Hiroaki; Moritani, Mako; Kitahara, Tadashi (Frontiers in Human Neuroscience, 2023)
We investigated the changes in lateral vestibulospinal tract (LVST) excitability and postural control after a dynamic balance intervention and the relationships between these changes. Twenty-eight healthy adults were randomly assigned to either the dynamic balance group or control group. They performed either a dynamic balance or static intervention for 10 trials of 30 seconds each and were assessed for head jerks during the intervention to confirm adaptation to the intervention. LVST excitability and postural stability were assessed before and after the interventions. LVST excitability was assessed as the change rate in the soleus H-reflex amplitude with galvanic vestibular stimulation (GVSH). The velocity and area of the center of pressure (COP) were examined in the eyes closed/foam rubber condition. No significant main and interaction effects (task, time) were observed for GVSH and COP variables. In the dynamic balance intervention, head jerk significantly decreased, and GVSH-change and changes in head jerk and COP area were significantly negatively correlated. The LVST excitability change for the dynamic balance intervention varied among the participants, although increased LVST excitability may have been related to increased postural stability.